Outcome of CBV (Carmustine, Cyclophosphamide, Etoposide) Conditioning Regimen for Autologous Stem Cell Transplant in Lymphoma: A Retrospective Study from a Tertiary Cancer Center in South India - Krishnamoorthi, Narendran; Prakash, Bhanu; KM, Dhanraju; Pani, Chinmaya Kumar; Ram, Malliha; Rajesh, Kalpana; Dubashi, Biswajit; Ganesan, Prasanth; Kayal, Smita (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction In autologous stem cell transplant (ASCT) for lymphomas, no standard conditioning regimen has been defined so far. Thus, the choice is guided by the center's familiarity and experience with a particular regimen.Objective To determine the response, toxicity, and survival outcomes in lymphoma patients who underwent ASCT with CBV (cyclophosphamide, carmustine, and etoposide) conditioning regimen.Materials and Methods Between January 2013 and May 2019, 45 consecutive lymphoma patients who had ASCT with CBV conditioning regimen were included in this retrospective study. CBV consisted of cyclophosphamide (1.5 g/m2/day × 4 days), carmustine (300 mg/m2 × 1 day), and etoposide (125 mg/m2 twice daily × 3 days). Baseline characteristics, pre transplant response, apheresis, post-transplant toxicities, post-transplant response, and survival outcomes were collected. Endpoints were toxicity, response, event-free survival (EFS), and overall survival (OS).Results The median age was 30 (range: 6–64) years. Diagnosis was Hodgkin lymphoma (HL) in 26 (58%) and non-Hodgkin lymphoma (NHL) in 19 (42%). Forty-three patients (95%) had chemosensitive disease; 22(49%) in CR, and 21 (46%) in PR. The median CD34 was 2.95 × 106/kg (range: 0.9–9.56). The median time to neutrophil engraftment was 11 days (9–23) and 13 (8–36) days for platelets. All patients had febrile neutropenia, clinically and/or microbiologically documented infection was seen in 75% of patients. The most common grade 3/4 toxicities were mucositis (n = 4, 9%), diarrhea (n = 4, 9%), and nausea/vomiting (n = 2, 4%). The average days of hospitalization was 18 (range: 10–37). Day 100 mortality was 6.6% (n = 3). The median follow-up was 44.8 months. The median EFS for the entire cohort was 23.8 months; for HL, the median EFS was not reached, and for NHL, it was 7.97 months (95% confidence interval [CI]: 1.57–14.37). The median OS for the entire cohort and for HL was not reached; for NHL, it was 24.3 months (95% CI: 0.56–48.11).Conclusion CBV conditioning regimen was well tolerated with low grade 3/4 toxicities and efficacy comparable to literature data.
Keywords: CBV conditioning regimen; autologous stem cell transplant; Hodgkin lymphoma; non-Hodgkin lymphoma